2018
DOI: 10.1098/rstb.2017.0413
|View full text |Cite
|
Sign up to set email alerts
|

Bridging cultural gaps: interdisciplinary studies in human cultural evolution

Abstract: One contribution of 16 to a theme issue 'Bridging cultural gaps: interdisciplinary studies in human cultural evolution'. Within the blink of an eye on a geological timescale, humans advanced from using basic stone tools to examining the rocks on Mars; however, our exact evolutionary path and the relative importance of genetic and cultural evolution in directing it remain a mystery. Our cultural capacities-to generate new ideas, to communicate and learn from one another, and to form vast social networks-togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, it would be interesting to assess the degree to which tools themselves become specialized in populations divided into specialized guilds [57]. To this end, interdisciplinary studies at the intersection of theory and empirical research on this topic are particularly important [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it would be interesting to assess the degree to which tools themselves become specialized in populations divided into specialized guilds [57]. To this end, interdisciplinary studies at the intersection of theory and empirical research on this topic are particularly important [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Acerbi, 2019;Henrich, 2015;Heyes, 2018;Laland, 2017;Mesoudi, 2011) and themed journal issues (e.g. Gelfand and Kashima, 2015;Kolodny et al, 2018;Whiten et al, 2017Whiten et al, , 2011. Moreover, recent research articles show that the study of cultural transmission is not only relevant for understanding what shaped human origins, but also to make sense of what is happening in the present, from the spread of news on social media (Weng et al, 2013) to healthy behaviour in social networks (Centola, 2010), and many other features of the 'information age'.…”
Section: Introductionmentioning
confidence: 99%
“…[1,11,[29][30][31]) and themed journal issues (e.g. [32][33][34][35]). Moreover, recent research articles show that the study of cultural transmission is not only relevant for understanding what shaped human origins, but also to make sense of what is happening in the present, from the spread of news on social media [36] to healthy behaviour in social networks [37], and many other features of the 'information age'.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, innovators act like cultural reservoirs and incubators that permit the selection of advantages (social, cultural or biological). 2,3 There is an important place for more variation of views and approaches and protection of local and personalised approaches to recovery, seeing patient as innovators. Exceptional people and exceptional views should be welcomed as avenues to improve mental healthcare.…”
mentioning
confidence: 99%
“…Recent research on the cultural transmission of innovation has shown how progressive and remarkable individuals (like Hawking) can have a disproportionate influence on advances in society, more so than shared social movements, as these face greater resistance, less diversity of opinion and inherent expectations of conformity. By contrast, innovators act like cultural reservoirs and incubators that permit the selection of advantages (social, cultural or biological) 2 , 3 . There is an important place for more variation of views and approaches and protection of local and personalised approaches to recovery, seeing patient as innovators.…”
mentioning
confidence: 99%